Rheological experiments at constant stress as efficient method to characterize polymeric materials - Münstedt, Helmut (Journal of Rheology, 2014)
Rheology has achieved a strong position for the characterization of polymeric materials during the last 40 years. Dynamic-mechanical measurements are widely used for this purpose. On several examples, this paper demonstrates the potential of creep-recovery whose application has still been rather limited. In many cases, dynamic-mechanical experiments suffer from the fact that for several reasons, the angular frequencies applied are not chosen low enough to reach the terminal regime for which relationships between rheological quantities and molecular parameters have been established. In creep and a subsequent recovery, the time scales can be extended into the stationary regime in the linear range of deformation, and therefore, creep recovery is an efficient method to directly determine the zero-shear viscosity η0 and the linear steady-state recoverable compliance Je0. For a polymer melt with long relaxation times, it is shown how time-dependent creep data converted into dynamic-mechanical quantities can be used to extend the frequency scale to the terminal regime. The power of Je0 and its temperature dependence is demonstrated for the analysis of the branching structure of a polymer. Furthermore, from such kind of measurements, interesting insights into the interactions between particles and matrix molecules in filled polymeric materials were obtained. As shown in elongational experiments, the steady state of deformation at a constant stress is reached at shorter times than at the corresponding constant strain rate. The experimental consequences are discussed. Another interesting aspect of creep is that a constant stress implies a constant capillary number. The advantage of this experimental condition for investigations of the droplet deformation in polymer blends is demonstrated. © 2014 The Society of Rheology.
Created from Fastlane, Scopus look-up